Researching the social aspects of dementia from a social work perspective - Mali, Jana (Metodološki zvezki, 2023)
The issues associated with dementia are challenging for social workers, who have a lotof direct contact with people with dementia, as well as their support networks. Thesenetworks play a key role in the care of people with dementia. Social workers differ fromother professionals in that they are aware of the urgency of attending to social justice, aswell as the implementation of human rights, participation and equality. Recognising theexperiences of people with dementia is of paramount relevance to social work, as it providesinsight into their needs and the aptness of existing forms of assistance in responding to theirneeds. Through this approach, those working in social work strive to find new forms of helpto enable people with dementia to live independently in their community. It is importantto find ways to involve people with dementia as active co-creators in the helping processand in exploring the social perspectives of dementia. In the present paper, we present theliterature review on experience of researching dementia from a social work perspective inSlovenia and Croatia - two countries with similarities in the development of social workand its research. The inclusion of people with Alzheimer’s disease or dementia in researchis very complex. Both professionals working with people with dementia (formal caregivers)and family members (mostly informal caregivers) face various difficulties and pressures. Itis therefore important to consider research ethics and respect existing legal frameworksand informed consent. An individualised approach should be used to include people withdementia in research to meet their need for personal worth and dignity (despite numerousmental and functional deficits). Ultimately, all research should strive to determine the truesituation of people with dementia and their needs, with the aim of using and developingtheir remaining abilities to improve the quality of life for both those people and those whoprovide care for them.
Keywords: demenca; dementia; ethics; etika; needs assessment; osebe z demenco; potrebe; social work; socialno delo; user’s perspective